2022
DOI: 10.1037/sah0000352
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of weight stigma and health behaviors.

Abstract: Public health campaigns that explicitly or implicitly stigmatize higher-weight individuals are proliferating. Underlying this trend is an assumption that weight stigma can promote healthier behavioral change. Substantial research comprising empirical studies, narrative reviews, and meta-analyses has linked weight stigma to poorer psychological and physical health. While many studies have investigated how weight stigma affected health behaviors such as dieting and exercise, additional work is needed to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 84 publications
(152 reference statements)
2
23
0
Order By: Relevance
“…Very few individuals in the encouraging condition had these concerns and exhibited more positive reactions to the message overall. These results are consistent with the literature on positivity (e.g., Clemens et al, 2021;Li et al, 2016) and overwhelming evidence in the obesity literature that shaming and stigmatization are ineffective and related to more negative health behaviors (see Zhu et al, 2022 for a review).…”
Section: Discussionsupporting
confidence: 90%
“…Very few individuals in the encouraging condition had these concerns and exhibited more positive reactions to the message overall. These results are consistent with the literature on positivity (e.g., Clemens et al, 2021;Li et al, 2016) and overwhelming evidence in the obesity literature that shaming and stigmatization are ineffective and related to more negative health behaviors (see Zhu et al, 2022 for a review).…”
Section: Discussionsupporting
confidence: 90%
“…Weight stigma may also lead to weight gain through behavioural mechanisms, such as impairing weight management. Those who experience weight stigma are more likely to report overeating and unhealthy eating, and reduced motivation to engage in physical activity (Tomiyama, 2014;Vartanian & Porter, 2016;Vartanian & Shaprow, 2008;Zhu et al, 2022). In line with this literature, previous longitudinal analyses using ELSA and HRS data showed that reporting weight stigma at baseline increased the odds of becoming and/or remaining obese over the follow-up period (Jackson et al, 2014;Sutin & Terracciano, 2013).…”
Section: Discussionmentioning
confidence: 60%
“…Weight stigma may also lead to weight gain through behavioral mechanisms, such as impairing weight management. Those who experience weight stigma are more likely to report overeating and unhealthy eating and reduced motivation to engage in physical activity (Tomiyama, 2014; Vartanian & Porter, 2016; Vartanian & Shaprow, 2008; Zhu et al, 2022). In line with this literature, previous longitudinal analyses using ELSA and HRS data showed that reporting weight stigma at baseline increased the odds of becoming and/or remaining obese over the follow-up period (Jackson et al, 2014; Sutin & Terracciano, 2013).…”
Section: Discussionmentioning
confidence: 99%